Safety assessment of buried natural gas pipelines with corrosion defects under the ground settlement. (November 2021) - Zheng, Ting; Liang, Zheng; Zhang, Liang; Tang, Song; Cui, Zhongyin
Highlights: Developed a 3D FE model for defective pipelines under the ground settlement. The presence of corrosion defects reduces the bearing capacity of the pipeline. Settlement displacement reduces the threshold pressure that causes the buckling failure of the pipeline. Obtained the quantitative relationship between corrosion defect area, surrounding soil parameters, settlement parameters and pipeline failure mode. Abstract: Local corrosion defects of the pipeline and the ground settlement in the geotechnical engineering problem area pose a huge threat to the integrity and safety of the buried steel pipeline. The existing researches mainly focus on the design and construction of new pipelines or the safety evaluation of completed pipelines. However, the impact of pipe segments with anomalies (e.g., corrosion defects) on pipeline integrity has not been clearly and fully considered. The novelty of this study lies in the development of a nonlinear pipe-soil coupling mechanical model considering the coupling effect of the typical ground settlement and local corrosion defects of the buried pipelines. Numerical results show that the developed model is feasible to evaluate the integrity and safety of corroded pipelines under the ground settlement.